Oxidative stress, hormones, and effects of natural antioxidants on intestinal inflammation in inflammatory bowel disease - Sahoo, Dipak Kumar; Heilmann, Romy M.; Paital, Biswaranjan; Patel, Ashish; Yadav, Virendra Kumar; Wong, David; Jergens, Albert E. (Frontiers in Endocrinology, 2023)
Inflammatory bowel disease (IBD) is a chronic, relapsing gastrointestinal (GI) disorder characterized by intestinal inflammation. The etiology of IBD is multifactorial and results from a complex interplay between mucosal immunity, environmental factors, and host genetics. Future therapeutics for GI disorders, including IBD, that are driven by oxidative stress require a greater understanding of the cellular and molecular mechanisms mediated by reactive oxygen species (ROS). In the GI tract, oxidative stressors include infections and pro-inflammatory responses, which boost ROS generation by promoting the production of pro-inflammatory cytokines. Nuclear factor kappa B (NF-κB) and nuclear factor erythroid 2–related factor 2 (Nrf2) represent two important signaling pathways in intestinal immune cells that regulate numerous physiological processes, including anti-inflammatory and antioxidant activities. Natural antioxidant compounds exhibit ROS scavenging and increase antioxidant defense capacity to inhibit pro-oxidative enzymes, which may be useful in IBD treatment. In this review, we discuss various polyphenolic substances (such as resveratrol, curcumin, quercetin, green tea flavonoids, caffeic acid phenethyl ester, luteolin, xanthohumol, genistein, alpinetin, proanthocyanidins, anthocyanins, silymarin), phenolic compounds including thymol, alkaloids such as berberine, storage polysaccharides such as tamarind xyloglucan, and other phytochemicals represented by isothiocyanate sulforaphane and food/spices (such as ginger, flaxseed oil), as well as antioxidant hormones like melatonin that target cellular signaling pathways to reduce intestinal inflammation occurring with IBD.